Palaeoclimate in the Low Tatras of the Western Carpathians during MIS 11–6: Insights from multiproxy speleothem records. (1st January 2022) - Błaszczyk, Marcin; Hercman, Helena
Abstract: Two speleothems from the Demänova Cave of Liberty, located in the Low Tatras in Slovakia, were studied in detail. Age-depth modelling based on U-series dating allowed us to constrain the growth period for both speleothems to between approximately 375 and 157 ka. Based on a multiproxy approach, it was possible to identify periods with dominant warm climatic conditions, which enabled long and continuous speleothem growth during most of the marine isotope stage (MIS) 9 and in MIS 7c. Unfavourable for speleothem growth climate included glacial conditions, such as in MIS 10 or MIS 8, and periods connected with diminished rainfall or lower temperature such as in MIS 9b, MIS 7e or MIS 7b. The growth interruptions of the speleothems are related to maximum glacial episodes like in MIS 10a and late MIS 6, or were connected with a decrease in rainfall in MIS 9a and cold, harsh climate conditions in MIS 7d. The obtained records suggest relatively mild glacial periods (MIS 8 and MIS 10) and warm interglacial periods (MIS 9 and MIS 7) enabling long periods of speleothem growth. Gathered results indicate a large diversity of climate conditions during MIS 7, with atypical MIS 7d major stadial occurring within the interglacial complex. Compared records also showed the important role of local factors and changes in the alimentation area, which affected the isotopic composition of speleothem and may cause significant differences in the isotope records from the same cave system, especially during intense climate changes. Highlights: A history of climatic changes from two Low Tatras speleothems. Stable isotope and trace element records covering the MIS 11a – MIS 6c period. The climate conditions of MIS 10, MIS 8 and MIS 6 enable speleothem growth. A large diversity of paleoclimate conditions during MIS 7 was recorded in speleothem.